Pandangan Ulama' Tentang Pemaksaan Berhubungan Badan Terhadap Istri Dalam Keadaan Sakit - Abdul Halim; Robiah Adawiyah (MASADIR: Jurnal Hukum Islam, 2022)
This study aims to find out how the views of scholars regarding coercion relate to wives in a sick state and how the legal istinbat used by scholars regarding coercion relates to wives when they are sick. The research method used is a qualitative method with the type of library research. From the results of the study, it can be concluded that if there is coercion in a relationship, according to scholars, the four schools of law are forbidden to harm physically, psychologically and healthily because in the prohibition law, it is feared that there are sexually transmitted diseases (pubic diseases). allow sexual intercourse even if you are sick, namely minor illnesses such as flu, cough, fever and runny nose. Imam Shafi'i's legal stint is in Surah An-Nisa' verse 19, Imam Maliki is quoted with the hadith of the prophet, namely the prohibition of intercourse like animals, while Imam Hambali is quoted with the hadith of the prophet, namely the actions of a'zl, and Imam Hanafi in his book explains that it is permissible to do so. intercourse by force if there is no syar'i udzur.